2021
DOI: 10.1111/myc.13371
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Transformation and Treatment Recommendations of Chronic Hyperplastic Candidiasis—A Six‐year Retrospective Cohort Study

Abstract: Background: Oral chronic hyperplastic candidiasis (CHC) is the most uncommon type of oral candidiasis with diverse manifestations. Up to date the diagnosis, long-term management and prognosis of this oral potentially malignant disorder remain obscure. Objectives:The aim of this study was to provide the recommendations guiding the diagnostic procedure, clinical management and prognosis assessment of CHC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Two articles were excluded on the basis of being case reports, whilst one last study was discarded due to its representation of in vitro research results (i.e., off-topic). Nine articles were finally selected to enter the systematic review [ 6 , 7 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. The reviewers’ intra-agreement was considered appropriate (κ = 0.83 [95% CI: 0.75–0.89].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two articles were excluded on the basis of being case reports, whilst one last study was discarded due to its representation of in vitro research results (i.e., off-topic). Nine articles were finally selected to enter the systematic review [ 6 , 7 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. The reviewers’ intra-agreement was considered appropriate (κ = 0.83 [95% CI: 0.75–0.89].…”
Section: Resultsmentioning
confidence: 99%
“…The studies reported a total of 274 patients with CHC. The nine reports included in the present review were conducted in different countries across three continents: Europe [ 7 , 20 , 21 , 22 , 23 , 24 ], Asia [ 6 , 25 ], and North America [ 26 ]. Whilst these reports were published between 1966 and 2021, most studies were case series or retrospective cohort studies, and the target population was always clinic-based.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous work revealed that 20.83% of chronic hyperplastic candidiasis (CHC) patients had varying degrees of epithelial dysplasia and 4.17% had malignant transformation. 20 Considering the potential association between C. albicans and OSCC, as well as the abilities of C. albicans to activate some signals involved in PD-L1 regulation, it is worthy of research to investigate the role of C. albicans in regulating PD-L1 expression in OSCC. In this study, we explored the expression of PD-L1 in OSCC cell lines and OSCC mice during C. albicans infection.…”
mentioning
confidence: 99%